"Cara a Times Square" or the path to the rejection of identity - Galiano Leis, Beatriz (Madrygal. Revista de Estudios Gallegos, 2013)
This paper is an approach to the topic of identity throw a personal and a national perspective in the novel Cara a Times Square. With this aim, the attention settles in three fundamental aspects: the anonymity of the characters, the use of great urban spaces and the recurrent subject matter of immigration.